Barrett's Esophagus and associations with esophageal mucosal Injuries (Research, Society and Development, 2022)
Introduction: Columnar epithelium in the distal esophagus and biopsies with intestinal metaplasia define Barrett's esophagus (EB). The objective was to identify the association of EB and esophageal mucosa lesions in histopathological reports. Methods: a retrospective and cross-sectional study with 1953 reports of esophageal mucosa. Results: 1953 biopsies of esophageal mucosa lesions were analyzed. We identified 133 (6.8%) of Barrett's esophagus, 151 (7.7%) with H.pylori and of these, 17 (11.3%) (p =0.041) were associated with Barrett's esophagus. The mean age group was 52 years old (IQR 42.5-62.5), male prevalence (63.2%). Lesions associated with EB: metaplasia 23 (17.3%) (p=0.004); dysplasia 8 (6%) (p